Paracentesis as an initial intervention in Malay Indonesian eyes with acute primary angle closure (Faculty of Medicine Universitas Indonesia, 2012)
Background: Acute primary angle closure (APAC) is one of the causes of blindness in Department of Ophthalmology Cipto Mangunkusumo General Hospital. Management of APAC is still controversial. Laser peripheral iridotomy is difficult to be done due to corneal edema as a result of persistent high intraocular pressure (IOP). It is believe that paracentesis will lower IOP immediately. The objective of the study was to assess outcome of paracentesis as the initial management in Malay Indonesian eyes with APAC. Methods: This intervention study was conducted at the Eye Clinic of Cipto Mangunkusumo Hospital and Jakarta Eye Center commencing in January 2005 until December 2007. Malay Indonesian eyes with APAC were included in this study in accordance with the new Asia Pacific consensus. All APAC eyes underwent paracentesis to lower IOP. The presenting and post-paracentesis IOP and peripheral anterior synechiae were noted. The outcome was termed as good when IOP was â¤ 21 mmHg and poor when IOP was > 21 mmHg. Results: A total of 45 APAC eyes were recruited. Thirty-eight of these belonged to women; mean age was 54.6 ± 1.56 years. Meanwhile, average duration of symptoms was 13.15 ± 7.4 days and mean of extent of peripheral anterior synechiae (PAS) was 7.7 ± 3.1 hours. There was a strong correlation regarding duration of symptoms to the formation of PAS (r = 0.672; p < 0.001). The mean presenting IOP was 55 ± 13.37 mmHg and mean post-paracentesis IOP was 27 ± 12.78 mmHg. A decrease of 49% in IOP ( p < 0.001) was observed after paracentesis with good outcome in 19 eyes and poor outcome in 26 eyes. Conclusion: Paracentesis as an initial intervention in APAC eyes reduces the IOP immediately, but only as a temporary response. (Med J Indones. 2012;21:113-7)